Searching Simkania negevensis in environmental waters - Pérez, Leonardo Martín; Codony, Francesc; Ríos, Karina; Peñuela, Gustavo; Adrados, Bárbara; Fittipaldi, Mariana; de Dios, Gregori; Morató, Jordi (Folia microbiologica, 2012)
Simkania negevensis is an obligate intracellular bacterium grouped into the order Chlamydiales. This new amoeba-resistant bacterium represents a novel aetiologic agent of bronchiolitis and community-acquired pneumonia in both adults and children. It has been suggested that Simkania could be an ubiquitous microorganism presented in water environments. In the natural history of infections with amoeba-related bacteria encountered in aquatic habitats, the transmissions by environmental aerosols or contaminated water/air systems have been extensively recognized. Therefore, understanding the feasibility of Simkania infection by these or similar routes is relevant. In the present work, we investigated the prevalence of this novel disease-associated microorganism in water samples from different sources by real-time PCR (qPCR). Our results show Simkania detection in 5 of 185 water analyzed samples (2.7%: 2 of 88 cooling towers and 3 of 8 waste water samples). However, no Simkania was detected in a drinking water.
Keywords: znečištění vody; Water Microbiology; Respiratory Tract Infections; Spain; infekce dýchací soustavy; mikrobiologie vody; Water Pollution; Chlamydiales; Španělsko